Integrated Change Management Approaches for Sustainable Learner Life Skills Development in the Digital Age - Suwanbamrung, Nareerat; Rungsiwantana , Chanudom; Intharasamai, Sunisa; Boonsong, Kanchana; Phetchsom, Nipa (Journal of MCU Phetchaburi Review, 2026)
Abstract This academic article aims to synthesize concepts and propose change management approaches suitable for developing learner life skills amidst the volatility of the Digital 4.0 era, where AI and IoT play crucial roles in daily life. The study reveals that life skills serve as a vital "mental vaccine" for learners; however, traditional school administration faces limitations in effectively cultivating these skills. This article proposes a new body of knowledge presented as an "Integrated Change Management Approach." This approach applies behavioral change theories to drive the four main areas of school administration through a three-phase process: 1) Planning and Unfreezing, to build awareness and analyze situations; 2) Implementing Change, driven through three dimensions: integrated learning, intensive activities, and a strong student support system; and 3) Maintaining and Refreezing, utilizing reflective processes (R-C-A) and effective resource allocation. The synthesis indicates that systematic and integrated change management will elevate schools into spaces that cultivate strong and sustainable life skills for learners in the digital age Keywords: Change Management, Life Skills, Digital Age, School Administration System